Partial characterization of Enterococcus faecalis bacteriophage F4 - Nigutová, Katarína; Štyriak, Igor; Javorský, Peter; Pristaš, Peter (Folia microbiologica, 2008)
Large Enterococcus faecalis F4 bacteriophage (described earlier) consisting of double-stranded linear DNA of approximately 60 kb was characterized. Library was prepared of its random DNA fragments and selected recombinants were sequenced. Three phage essential genes were characterized: DNA polymerase, replicative DNA helicase and a minor capsid protein, showing only limited homology to other known phage encoded genes. The occurrence of these genes among enterococci was determined by PCR method. Only two out of 40 tested isolates possessed all three genes, another three isolates contained at least one of the genes, demonstrating low frequency F4 lysogens among natural enterococcal isolates.
Keywords: Enterococcus faecalis; Sequence Analysis, DNA; genom virový; lyzogenie; Lysogeny; Genome, Viral; Molecular Sequence Data; molekulární sekvence - údaje; sekvenční analýza DNA; Bacteriophages; bakteriofágy; polymerázová řetězová reakce; Polymerase Chain Reaction; Viral Proteins; virové proteiny